2011
DOI: 10.1200/jco.2010.30.7678
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled, Phase II Trial of Sorafenib and Erlotinib or Erlotinib Alone in Previously Treated Advanced Non–Small-Cell Lung Cancer

Abstract: Although there was little difference in ORR or PFS, subset analyses in EGFR WT and EGFR FISH-negative patients suggest a benefit for the combination of erlotinib/sorafenib compared with single-agent erlotinib with respect to PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 29 publications
3
107
0
2
Order By: Relevance
“…However, subset analyses by Spigel et al in the trail showed a benefit in EGFR WT and EGFR FISH-negative patients for the combination of erlotinib/ sorafenib compared with single-agent erlotinib with respect to PFS and OS (Spigel et al, 2011). Similarly, a multicenter phase II study of erlotinib and sorafenib in chemotherapy-naive patients with advanced non-small cell lung cancer also suggested that patients with wildtype EGFR had a higher ORR than previously reported for single-agent erlotinib/sorafenib (Lind et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, subset analyses by Spigel et al in the trail showed a benefit in EGFR WT and EGFR FISH-negative patients for the combination of erlotinib/ sorafenib compared with single-agent erlotinib with respect to PFS and OS (Spigel et al, 2011). Similarly, a multicenter phase II study of erlotinib and sorafenib in chemotherapy-naive patients with advanced non-small cell lung cancer also suggested that patients with wildtype EGFR had a higher ORR than previously reported for single-agent erlotinib/sorafenib (Lind et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In previouslytreated NSCLC patients, sorafenib also failed to show additional benefits in combination with pemetrexed in a phase II trial (Molina et al, 2011). In a randomized, double-blind, placebo-controlled Phase II trial of sorafenib and erlotinib or erlotinib alone, sorafenib did not statistically improve DCR , PFS and OS when combined with erlotinib in patients with relapsed NSCLC (Spigel et al, 2011). Nevertheless, another Phase III clinical trial NExUS still showed a clinically modest but statistically significant prolongation in progression-free survival for the sorafenib plus cisplatin/gemcitabine arm compared to cisplatin/ gemcitabine alone (6.1 versus 5.5 months, p<0.001) (PazAres LG et al, 2012).…”
Section: Wei-lan Wang Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Drug-related bleeding was observed in four patients and hemorrhagic/bleeding and neurological events were more common in patients with SCC (37.5% and 75%, respectively) compared to other histology. A phase II trial evaluated the efficacy of sorafenib plus erlotinib vs. placebo plus erlotinib in patients with advanced NSCLC, pretreated with one or two regimens (63 …”
Section: Sorafenibmentioning
confidence: 99%